Morphology of potassium sodium niobate based silicate glass system - Ploypailin Yongsiri (2018)
In this research, the fabrication of lead-free ferroelectric glass-ceramics from the (K 0.5 Na 0.5 )NbO 3 system via incorporation method was carried out. For the incorporation method, calcined KNN was added into glass batches as a heterogeneous nucleating agent. Glass-ceramics KNNs were prepared from two compositions of KNN-SiO 2 with a ratio of 75: 25 (C1) and 80: 20 (C2) mol.%. Thermal properties resulting from DTA showed samples C1 and C2 having glass transition temperatures of 532°C and 520°C and crystallization temperatures of 645°C and 620°C, respectively. The prepared glasses were subsequently subjected to a heat treatment schedule in a temperature range of 500°C - 575°C for crystallization. XRD results showed that the KNN phase occurred in C1. The C2 glass-ceramic samples contained unidentified phases together with the KNN phase. From SEM observation, it was found that bulk crystals with an equiaxed shape of KNN phase dispersed well in all glass-ceramic matrices. Crystal sizes increased with increasing heat treatment temperatures. In C2 glass-ceramics, unidentified phases were found together with the KNN phase. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.